Nutritional Status of Pre-School Children of Pokhara- Lekhanath Metropolis, Kaski - Poudel, Gyanendra Raj (Journal of Health Promotion, 2018)
The study is aimed at finding out the nutritional status of pre-school children with relation to occupation, annual income and education status of their parents. The study is based on descriptive research design. Weight for height, height for age, and weight for age were the main areas of nutritional status of children which were measured using primary data only. The study has been carried out in Ward no 9, 10 and 11 of Pokhara Lekhnath Metropolis, Kaski. There were 15 pre-schools in the study area. Among them, 6 pre-schools were taken by the convenient sampling method and from each pre-school 20 children were chosen by the lottery method. Their parents were also included in the population of the study. The study reveals that the majority of the respondents are engaged in different services in Nepal and the nutritional status of their children was found better than Nepal's national nutritional standard. The children, whose parents have yearly income of 2 to more than 6 lakhs, have better nutritional status. Likewise, in this study, not a single mother is illiterate; it has been revealed that the mother's educational standard is the reason behind children's poor nutritional status.Journal of Health Promotion Vol.6 2008, p.18-22